Dynamic processes permitting stable coexistence of antimicrobial resistant and non-resistant organisms in a gastrointestinal tract model - Tippawan Puttasontiphot (2018)
In this paper, bacteria-antibiotic dynamics in a gastrointestinal tract exposed to antimicrobial selection pressure is modeled as occurring in a continuous chemostat. Two populations of microorganisms, one sensitive and the other resistant to an inhibitor, namely an antibiotic, compete for a single limiting resource. It is shown that conditions exist whereby the two types of bacteria can persist. Application of the singular perturbation analysis also yields delineating conditions on the "effective" antibiotic level that encode information on the minimum inhibitory concentration (MIC) and the minimum antibiotic concentration (MAC), which are extremely important parameters commonly used to quantify the activity of antibiotics against a given bacterium.